Voltaire’s Radicalism - Drozdowicz, Zbigniew (Wydawnictwo Uniwersytetu Jagiellońskiego, 2014)
This article reminds the reader of the views of Voltaire, one of the most prominent and influential philosophers of the Age of Enlightenment. Voltaire’s radicalism manifested itself mainly in anticlericalism which was consistent, uncompromising and voiced without mincing words. A general aim of this article is to demonstrate to his contemporary imitators, who can be found in different countries including Poland, that they are in fact more or less accurate copies of him and they are not always aware of whom they imitate and what value this imitation has. Perhaps this article can make them, if not more restrained in their statements and practical actions, at least more self-critical and taking into account what is expressed in public discourse.
Keywords: anticlericalism; deism; radicalism; Voltairianism